Mobile Health Intervention to Improve Uptake and 12-Month Continuation of Long-Acting Reversible Contraception Among Urban Female Adolescents: A Multicenter Randomized Controlled Trial - Rizky Ayu; Sana Ullah; Immanuel Simbolon (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Adolescent pregnancy remains a major source of obstetric and psychosocial morbidity in densely populated Indonesian cities. Long-acting reversible contraception (LARC) offers first-line efficacy, yet adolescent uptake and continuation are constrained by misinformation and stigma. Mobile health (mHealth) may bridge this gap discreetly. We evaluated whether an interactive, encrypted mHealth platform improves LARC uptake and 12-month continuation versus standard care. Methods: We conducted a parallel, two-arm (1:1), open-label multicenter randomized controlled trial with blinded outcome assessment at two tertiary reproductive-health centers in Jakarta and Palembang, Indonesia. Sexually active women aged 15–21 years not desiring pregnancy within 12 months were block-randomized (stratified by center and parity). The platform delivered interactive education, private counselor chat, and automated reminders. Primary outcomes were LARC uptake at 1 month (intention-to-treat) and time-to-discontinuation over 12 months, analyzed with risk ratios (RR), Kaplan–Meier survival, Cox regression, and number needed to treat (NNT). Results: Of 390 adolescents screened, 364 were randomized (182 per arm). LARC uptake was 36.8% with mHealth versus 16.5% with standard care (RR 2.23, 95% CI 1.53–3.26; adjusted odds ratio 2.95, 95% CI 1.80–4.84; p<0.001). Absolute risk reduction was 20.3% (NNT 5). The 12-month continuation rate was 82.1% versus 56.7% (log-rank p=0.014), and Cox regression showed a 62% lower discontinuation hazard (adjusted hazard ratio 0.38, 95% CI 0.17–0.85; p=0.018). Conclusion: An encrypted, interactive mHealth intervention more than doubled LARC uptake and improved 12-month continuation among urban Indonesian adolescents, supporting integration of scalable, stigma-sensitive digital platforms into adolescent family-planning services.